Application of Geographic Information System for Evaluating Agricultural Potential Land Class in Nakhon Nayok Province. - Sakunpet, Alongkron; Intaravicha, Nuttakorn; Maksuwan, Atirat (Journal of Vocational Education in Agriculture, 2020)
The objective of this research was to evaluate Agricultural Potential Land Class (APLC) based on 5 APLC criterias including elevation, soil order, irrigation system, soil moisture regimes and soil pH. This research used Application of Geographic Information System(GIS) to analyse and develop spatial model to classify 6 APLC orders; APLC1 Commercial Farming (CF), APLC2 Sufficient Farming (SF), APLC3 Urban and Industrials (U&I), APLC4 Biomass Plant (BP), APLC5 Economic Forest (EF) and APLC6 Natural Conserve (NC). The results showed that the Agricultural Potential Land of Nakhon Nayok Province were Commercial Farming (CF), Sufficient Farming (SF), Urban and Industrials (U&I), Biomass Plant (BP) andEconomic Forest (EF) were 14,746.72 rai (1.10%), 60,4252.36 rai (45.16%), 24,0588.06 rai (17.98%), 66,456.98 rai (4.97%), 60,121.88 rai (4.49%) and 351,937.08 rai (26.30%) respectively.